REPRESENTING SOCIAL RELATIONS THROUGH ADDRESS TERMS IN ZOOTOPIA - Syifa Zahra; Muhammad Hafiz Kurniawan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates how terms of address in Disney’s Zootopia represent social relations, particularly unequal power relations and interpersonal closeness. Terms of address in conversation reflect various aspects of social relationships, including power relations, social distance, frequency of interaction, and emotional closeness. Employing a qualitative discourse analysis approach, the study analyzes address terms used by characters in both formal and informal interactions throughout the film. The study addresses two research questions: (1) How do terms of address reveal unequal power relations in formal settings? And (2) How do terms of address reveal interpersonal closeness in informal situations? The analysis integrates Eggins’ theory of tenor within the interpersonal metafunction framework and van Leeuwen’s theory of social actor representation. The findings reveal that formal interactions are predominantly characterized by formalization (71.4%) and honorification (87%), indicating the influence of institutional hierarchy and social distance on language choice. In contrast, informal interactions are dominated by appraisement (55.7%) and informalization (68.4%), reflecting familiarity, emotional closeness, and frequent social contact among characters. The findings demonstrate that address terms function not only as linguistic markers of identity but also as indicators of social hierarchy and interpersonal relationships. However, since this study focuses solely on a single animated film as a representation of social relations, future studies are encouraged to compare address-term usage across different films, genres, or cultural contexts.